True aneurysmal dilatation of a valved bovine jugular vein conduit after right ventricular outflow tract reconstruction: a rare complication. (8th August 2019) - Yoldaş, Tamer; Örün, Utku A.; Tak, Sercan
Abstract: Valved bovine jugular vein conduit is considered a suitable choice for paediatric population with congenital heart defect requiring right ventricle to main pulmonary artery connection. However, complications related to the use of this device have been reported, with conduit failure occurring mainly as a consequence of stenosis, conduit thrombosis, and valve regurgitation. We present a case of aneurysmal conduit failure of a valved bovine jugular vein conduit used to reconstruct the right ventricular outflow tract.